1995
DOI: 10.1093/oxfordjournals.aje.a117577
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Preterm Delivery in Two Birth Cohorts with an Interval of 20 Years

Abstract: The occurrence and determinants of preterm delivery were studied in two population-based birth cohorts from northern Finland. In the first cohort of 1966 there were 11,475 singleton deliveries and in the later cohort of 1985-1986, 8,888. The overall incidence (percentage) of preterm deliveries fell from 9.1 to 4.8, including a reduction from 8.8 to 3.4 for spontaneous preterm deliveries. For iatrogenic ones, however, there was an increase from 0.3 to 1.4. The relative risks, associated with such known maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 0 publications
1
62
0
5
Order By: Relevance
“…Socioeconomic disparities in PTB are consistent findings in perinatal epidemiology both in Sweden, other European countries, and the U.S. [22][23][24][25][26][27]. For example, even in such countries as Sweden [28], Finland [29], Scotland [30], and Canada [31] with smaller socioeconomic differences than in the U.S. and universal access to high-quality prenatal care [22], there are higher rates of PTB among mothers with low income than those with high income. A Canadian case-control study found that mothers with low income had a three-fold increased odds of having preterm premature rupture of membranes [32].…”
Section: Discussionmentioning
confidence: 73%
“…Socioeconomic disparities in PTB are consistent findings in perinatal epidemiology both in Sweden, other European countries, and the U.S. [22][23][24][25][26][27]. For example, even in such countries as Sweden [28], Finland [29], Scotland [30], and Canada [31] with smaller socioeconomic differences than in the U.S. and universal access to high-quality prenatal care [22], there are higher rates of PTB among mothers with low income than those with high income. A Canadian case-control study found that mothers with low income had a three-fold increased odds of having preterm premature rupture of membranes [32].…”
Section: Discussionmentioning
confidence: 73%
“…Predisposing genetic attributes, pre-existing and emerging parental biological and behavioural factors, and social and economic circumstances have all been found to contribute (either in concert or isolation) to the risk of preterm birth. [11][12][13][14][15][16] A number of studies have suggested that obstetric complications and pre-existing medical conditions, moderated by sociodemographic factors, may influence a clinician's decision to induce labour based on the perceived threat of neonatal mortality or serious morbidity. 17,18 Clinicians' perception of risk may also have changed over time, favouring intervention at lower perceived levels of risk to avoid potential complications for mother and child.…”
Section: Introductionmentioning
confidence: 99%
“…10 The trend towards being unmarried during pregnancy is increasing: in 1989 22.9% and in 2001 39.2% of pregnancies in our study population were outside marriage; and a comparable change has taken place in all Western countries. 10,11 It has been suggested that the additional risks of extramarital pregnancies are higher in societies where pregnancies outside marriage are uncommon; in a recent French study a cutoff point of 20% of births to unmarried mothers was suggested to divide societies into those with high risks of adverse pregnancy outcomes outside marriage and those with no excess risks of pregnancies outside marriage. 4 Unmarried status may reflect other risk factors rather than being an independent risk factor.…”
Section: Introductionmentioning
confidence: 99%
“…13 In previous studies at least some of the risks have been suggested to be the result of inadequate access to maternity care. 4,11,14 However, in Finland maternity care is provided free of charge and is used virtually by the entire pregnant population, up to 99.7%. 15 The opportunity to receive maternity care during pregnancy is not affected by the economic situation of a woman; this asset should lower the risks associated with unmarried status during pregnancy.…”
Section: Introductionmentioning
confidence: 99%